The Phenomenon of Bullying in School Environments: Strategies and Challenges - Noviyanti, Noviyanti; Hartini, Sri; Marlina, Leni; Oktarini, Melly (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Bullying is a complex phenomenon that requires a holistic approach to addressing it. Preventive efforts are a critical first step. Anti-bullying education in schools, teacher and staff training, and awareness campaigns involving students can encourage cultural and behavioral change. Activities that promote empathy and collaboration also play a role in building an environment that supports positive interpersonal relationships. An intervention approach is needed to address bullying cases that have already occurred. Safe and confidential reporting mechanisms give victims or witnesses the courage to speak up. In addition, counseling for victims and perpetrators helps deal with the emotional impact while addressing the root of the problem. Parent and community involvement strengthens these efforts, making bullying a shared responsibility. Technology also plays a strategic role in bullying prevention, especially in addressing new challenges such as cyberbullying. Digital applications and platforms for reporting bullying cases facilitate quick and confidential reporting. In addition, monitoring online activity through collaboration with parents and internet service providers is key to protecting students from online threats. However, a number of challenges still hinder the effectiveness of this strategy. Lack of awareness and support makes anti-bullying programs difficult to implement, especially in environments that have a culture that is permissive of such behavior. Limited resources, such as budget, expertise, and facilities, also limit the ability of schools and communities to address bullying comprehensively. Meanwhile, the rise of cyberbullying adds complexity, given its anonymous nature and wide reach in the digital world. To meet this challenge, collaboration between schools, families, communities, and governments is essential. With a comprehensive and sustainable approach, bullying can be prevented and addressed more effectively, creating a safer, healthier, and more inclusive environment for all.